2011
DOI: 10.1111/j.1440-1681.2011.05640.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 11β‐hydroxysteroid dehydrogenase 1 by carbenoxolone affects glucose homeostasis and obesity in db/db mice

Abstract: 1. One of the major causes of metabolic syndrome is elevated 11β-hydroxysteroid dehydrogenase 1 (11β-HSD1) in the liver and adipose tissue. High 11β-HSD1 expression contributes significantly to the diabetic phenotype in db/db mice. The purpose of the present study was to test the effect of the pharmacological inhibition of 11β-HSD1 inhibition by carbenoxolone in db/db mice, a genetic model of diabetes. 2. Inhibition of 11β-HSD1 by carbenoxolone was evaluated in liver homogenates obtained from untreated mice. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
(62 reference statements)
2
14
0
Order By: Relevance
“…Therefore, we decided to filter preparations through a 100 lm cell strainer, as reported by Salvalaggio et al (2002). Other reports included an extra step of purification by handpicking after applying this protocol (Daniel et al 2011;Dhanesha et al 2012;Mosedale et al 2012;Pang et al 2010) and our results further confirm the improvement of islet purity after adding this extra step.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, we decided to filter preparations through a 100 lm cell strainer, as reported by Salvalaggio et al (2002). Other reports included an extra step of purification by handpicking after applying this protocol (Daniel et al 2011;Dhanesha et al 2012;Mosedale et al 2012;Pang et al 2010) and our results further confirm the improvement of islet purity after adding this extra step.…”
Section: Discussionsupporting
confidence: 71%
“…CBX is known as a global disruptor of gap junction assembly, used to study the nonspecific blockage of Cxs, and our results revealed an antileukemic effect which was synergistic with Ara-C. CBX blocks the assembly of Cxs in the gap junctions and regulates the transfer of mi-RNA and several metabolites such as Ca 2+ and glucose. Moreover, it has been described that CBX inhibits 11β-hydroxysteroid deshydrogenase [39], but this enzyme was not expressed in the leukemic cells. Cancer cell survival is linked to the cell metabolism pathways including glycolysis, OXPHOS as well as amino acids and fatty acids metabolism [48].…”
Section: Discussionmentioning
confidence: 99%
“…The antileukemic effects of CBX cannot be explained by off target effects on 11β-hydroxysteroid deshydrogenase ( Supplementary Fig. S8a) [39]. HSD11B1 mRNA was not detectable in 22 AML cell lines and 11β-hydroxysteroid deshydrogenase protein was not found or induced by CBX in six AML cell lines ( Supplementary Fig.…”
Section: Cbx Reduces Heterocellular Communication Between Kg1a and Bmmentioning
confidence: 98%
“…Therefore, we cannot exclude that after sustained administration CBX might interact with other yet undetermined targets, exerting direct or indirect effects on the emotional parameter investigated here. CBX is known to inhibit the 11β‐hydroxysteroid dehydrogenase therefore competing with the synthesis of endogenous corticosterone which is itself known to regulate the expression of astroglial Cxs . It was also shown that CBX binds, albeit with a low affinity, to mineralo‐ and gluco‐corticoid receptors .…”
Section: Discussionmentioning
confidence: 99%